2016
DOI: 10.1111/gbb.12356
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the canine Oxtr gene: populations, variants and functional aspects

Abstract: Oxytocin receptor (OXTR) acts as a key behavioral modulator of the central nervous system, affecting social behavior, stress, affiliation and cognitive functions. Variants of the Oxtr gene are known to influence behavior both in animals and humans, however, canine Oxtr polymorphisms are less characterized in terms of possible relevance to function, selection criteria in breeding and domestication. In this report, we provide a detailed characterization of common variants of the canine Oxtr gene. In particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…Five novel (-213AG, -94TC, -74CG, -50CG, 19208AG) and three known (rs22927829, rs8679682, rs8679684) SNPs were found and genotyped in larger populations involving German Shepherds (N=71), Border Collies (N=104), Labrador-and Golden Retrievers (N=64), Beagles (N=29) and wolves (N=44). The results confirmed that the identified SNPs are polymorphic not only in the dog breeds, but also in wolves, however allele frequencies differed among the investigated breeds as well as between dogs and wolves.These results have recently been confirmed and extended(Bence et al, 2017) by investigating a large population involving nearly 700 dogs from 10 different breeds (Beagle, N=70; Border…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Five novel (-213AG, -94TC, -74CG, -50CG, 19208AG) and three known (rs22927829, rs8679682, rs8679684) SNPs were found and genotyped in larger populations involving German Shepherds (N=71), Border Collies (N=104), Labrador-and Golden Retrievers (N=64), Beagles (N=29) and wolves (N=44). The results confirmed that the identified SNPs are polymorphic not only in the dog breeds, but also in wolves, however allele frequencies differed among the investigated breeds as well as between dogs and wolves.These results have recently been confirmed and extended(Bence et al, 2017) by investigating a large population involving nearly 700 dogs from 10 different breeds (Beagle, N=70; Border…”
mentioning
confidence: 57%
“…breed effects. Some studies have already shown that different dog breeds differ in allele frequency for certain OXTR polymorphisms (Bence et al, 2016), and that these polymorphisms, as well as IN-OXT treatment can have differential effects in case of different breeds (Kis et al, 2014a;Kovács et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, whereas the pet dog population was heterogeneous with respect to breed, age and body size, the assistance dog population consisted entirely of young retriever dogs. Given potential for breed differences in OT genetics (Bence et al, 2016) future investigations of possible differences between pet and selectively bred working populations will benefit from designs controlling for these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, whereas the pet dog population was heterogeneous with respect to breed, age and body size, the assistance dog population consisted entirely of young retriever dogs. Given potential for breed differences in OT genetics (Bence et al, 2016 ) future investigations of possible differences between pet and selectively bred working populations will benefit from designs controlling for these parameters. Similarly, many individuals in the assistance dog sample were intact at the time of testing, whereas all pet dogs were sterilized.…”
Section: Methodsmentioning
confidence: 99%